Antioxidant Activity of Endophytic Bacterial Extract Isolated from Clove Leaf (Syzygium aromaticum L.) - Sogandi, Sogandi; Triandriani, Widya; Saputri, Dina; Suhendar, Usep (Journal of Agriculture and Applied Biology, 2020)
Clove (Syzygium aromaticum L.) is one type of spice plant that has high antioxidant content because of the high eugenol compounds. However, iso-lating these bioactive compounds require a significant amount of biomass. A known alternative solution to overcome the problems is through the utiliza-tion of endophytic bacteria in clove leaves. Endophytic cloves leaf bacteria can be a good antioxidant resource. Endophytic bacteria are bacteria that grow in plant tissues that is not pathogenic, which can replace these plants. The aim of this study is isolating endophytic bacterial from clove leaves, screening endophytic bacteria, determining potential endophytic bacteria as producer antioxidant compounds, and identifying potential isolate using 16S rRNA. This study used endophytic bacteria isolated from clove leaves (Syzygium aromaticum L.). Antioxidant activity determined using DPPH method. It was founded 7 isolates of endophytic bacteria namely WDY1, WDY2, WDY3, WDY4, WDY5, WDY6, and WDY7. The isolate WDY6 shows the highest antioxidant activity. WDY6 isolate is identical to Staphylococcus sp. with a 100% similarity. Staphylococcus sp. has the highest antioxidant activ-ity in the stationary phase. The content of chemical compounds from WDY6 isolates is pyrazine that belongs to alkaloids.